EXTH-18. IL-12 ARMORED CAR T CELL THERAPY FOR HETEROGENEOUS GLIOBLASTOMA. (12th November 2021) - Shen, Steven; Reedy, Jessica; Suryadevara, Carter; Hotchkiss, Kelly; Snyder, David; Sanchez-Perez, Luis; Sampson, John
Abstract: INTRODUCTION: Glioblastoma (GBM) is a lethal primary malignant brain tumor with a median survival of < 20 months. Our next generation immunotherapy utilizes chimeric antigen receptor (CAR) T cells targeted to GBM-specific overexpression of epidermal growth factor receptor variant III (EGFRvIII), "armored" with IL-12, a stimulatory cytokine that enhances T cell persistence and function, to treat orthotopic heterogeneous GBM. METHODS: C57Bl/6 mice were intracranially implanted with 5 x 10 5 of either CT2AvIII tumor cells or a 1:1 mixture of CT2AvIII and CT2A parental tumor cells. Seven days post-implant, mice were treated with 2 x 10 6 IL-12 CARvIII and monitored for survival. For endogenous T cell activity assessment, TCRα  -/- mice were intracranially implanted with either CT2AvIII cells or a 1:1 mixture of CT2AvIII:CT2A parental cells and treated 7 days post implant with intracranial IL-12 CARvIII therapy. RESULTS: IL-12 CARvIII therapy was curative in the treatment of CT2AvIII homogeneous tumors and confers a long-term survival in 50% of CT2AvIII:CT2A mice. Furthermore, IL-12 CARvIII therapy successfully eradicated the homogeneous CT2AvIII tumors in TCRα-/- mice but failed to produce any efficacy against the heterogeneous CT2AvIII:CT2A parental tumors, suggesting that endogenous T cells are required for IL-12 CARvIII therapeutic success against heterogeneous tumors. CONCLUSIONS: Our findings suggest that IL-12 CARvIII may be an effective treatment against heterogeneous glioma. Furthermore, this data provides insight on treatment against the immunosuppressive tumor microenvironment and applications against other solid tumors. In anticipation of translating this therapy into a phase I clinical trial, we are also investigating adjuvant therapies such irradiation to improve antitumor efficacy of IL-12 CARvIII against heterogeneous glioma.